Examining the Therapeutic Effects of Bioactive Compounds in Orange and Pomegranate for the Management of Acne Vulgaris - Hamza, Muhammad; Aftab, Rameesha; Saleem, Fizza; Umar Chaudhary, Ayesha; Anjum, Zahin; Saeed, Samina; Shahid, Komal; Fatima, Memoona; Fatima, Ghulam (Indus Journal of Bioscience Research, 2024)
Background: Acne vulgaris is the most common inflammatory skin disorder that affects millions of people globally. Various conventional treatments like topical retinoid as-well-as antibiotics are commonly used, but they have many limitations and side effects. But nutraceuticals are gaining much attention for their therapeutic potential in overall skin health and management of skin disorders especially acne. Objective: The main objective of this review was to examine the therapeutic potential of bioactive compounds present in orange and pomegranate for the management of acne vulgaris, due to their antioxidant, antimicrobial and anti-inflammatory properties. Materials and Methods: A comprehensive literature review was conducted using databases such as PubMed and Google Scholar. Studies examining the bioactive compounds of orange and pomegranate and their effects on acne-related factors such as inflammation, sebum production, and bacterial growth were included. Results: Results from the present review demonstrates that pomegranate contains bioactive compounds like ellagic acid and punicalagins, while orange contains flavonoids, hesperidin and vitamin C that have strong antimicrobial, anti-inflammatory, and antioxidant properties against acne-causing bacteria like P. acnes and Staphylococcus aureus. Conclusion: Nutraceuticals derived from natural food sources like pomegranate and orange demonstrate the therapeutic potential against the acne causing bacteria. Although existing studies suggested their beneficial effects but further clinical trials are still needed in order to fully establish their efficacy as well as to develop the optimized formulations for the oral and topical use against the treatment of acne